2020
DOI: 10.1111/are.14635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein levels on activities of protease and expression of ingestion and protein digestion‐related genes in Nile tilapia juveniles

Abstract: While some studies have investigated the effects of dietary protein on the activities of protease in Nile tilapia, little information exists about these enzymes and hormones regulating appetite at the molecular level. Therefore, we investigated the performance, protease activities and expression of genes related to protein intake and digestion in juvenile tilapia fed with diets containing different levels of crude protein (CP): 25.14, 31.12, 36.60 and 42.05%. The fish were fed to apparent satiation three times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Although these genes can regulate the synthesis of pepsinogen, trypsinogen, and chymotrypsinogen, the activations are also related to the specific environment in the gastrointestinal tract. Some studies have reported that protease activity is affected by both intrinsic and extrinsic factors, such as the physiological stage and health status of the organism, nutrient level of the feed, temperature, and exogenous protease (Liu et al, 2019;Choi et al, 2020;Hassani et al, 2020;Santos et al, 2020a;Santos et al, 2020b).. The feed, living environment, species, and physiological stage among the Japanese flounder used in this study have no differences.…”
Section: Digestion and Metabolism Of Proteinmentioning
confidence: 66%
See 2 more Smart Citations
“…Although these genes can regulate the synthesis of pepsinogen, trypsinogen, and chymotrypsinogen, the activations are also related to the specific environment in the gastrointestinal tract. Some studies have reported that protease activity is affected by both intrinsic and extrinsic factors, such as the physiological stage and health status of the organism, nutrient level of the feed, temperature, and exogenous protease (Liu et al, 2019;Choi et al, 2020;Hassani et al, 2020;Santos et al, 2020a;Santos et al, 2020b).. The feed, living environment, species, and physiological stage among the Japanese flounder used in this study have no differences.…”
Section: Digestion and Metabolism Of Proteinmentioning
confidence: 66%
“…Protein is one of the most important nutrients for organisms because it participates in essential physiological processes, such as the maintenance and repair of damaged tissues and the production of enzymes, hormones, and antibodies, through the anabolism and catabolism of protein during growth and reproduction (Tu et al, 2015;Santos et al, 2020a;Santos et al, 2020b). Proteases are enzymes that specifically break peptide bonds between amino acids during protein degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of protease will vary with the level of protein intake. In addition, dietary protein modulates the activity of alkaline proteases as well as the expression of these protease genes and hormones involved in appetite regulation [ 22 ]. The digestive enzyme pattern can reflect the feeding habit of fish which the quantity and composition of the diet can influence.…”
Section: Resultsmentioning
confidence: 99%